Water-based resin dispersion, composition having water-based resin dispersion as raw material, and layered body containing dry product of composition
A water-based resin dispersion with specific polymer compositions addresses the challenge of enhancing adhesion and low-temperature heat-sealability of polyolefins, offering improved bonding and sealing properties for polyolefin materials.
Patent Information
- Application Number
- JP2024168816
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-02-26
- Filing Date
- 2024-09-27
- Publication Date
- 2024-12-19
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing methods for improving the paintability and adhesiveness of polyolefins, such as propylene polymers, often require special equipment and do not sufficiently enhance low-temperature heat sealability and adhesion to polyolefin base materials.
A water-based resin dispersion containing a polymer A with olefinic monomer units and a polymer B with radically polymerizable monomer units, formulated to have specific elastic modulus and elongation properties, allowing for excellent adhesion and low-temperature heat-sealability to polyolefin materials.
The dispersion enables easy bonding of polyolefin materials with low-temperature and short-time heating, providing a laminate with improved adhesion and heat-sealability, suitable for applications like food packaging.
Smart Images

Figure 2024177221000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to an aqueous resin dispersion, a composition made from the aqueous resin dispersion, and a laminate comprising a dried product of the composition. This application claims priority based on Japanese Patent Application No. 2021-029842, filed on February 26, 2021, the contents of which are incorporated herein by reference. [Background technology]
[0002] Polyolefins such as propylene-based polymers and propylene-α-olefin copolymers are inexpensive and have excellent mechanical properties, heat resistance, chemical resistance, water resistance, etc., and are therefore used in a wide range of fields. However, since the polyolefins do not have polar groups in their molecules, they are generally low polar, making them difficult to paint or adhere to, and there has been a demand for improvements in paintability and adhesion. In order to improve paintability and adhesion, various methods have been attempted, such as chemically treating the surface of a polyolefin molded body with a chemical or the like, or oxidizing the surface of the molded body by corona discharge treatment, plasma treatment, flame treatment, etc. However, all of the above methods not only require special equipment, but also do not necessarily provide sufficient improvements in paintability and adhesion.
[0003] Therefore, modified polyolefins such as chlorinated polypropylene, acid-modified propylene-α-olefin copolymer, and acid-modified chlorinated polypropylene have been proposed as a method for imparting good coating properties and adhesion to polyolefins, such as propylene-based polymers, in a relatively simple manner. The modified polyolefins are generally characterized in that they can be applied to the surface of a polyolefin molded body as a surface treatment agent, adhesive, paint, or the like. The modified polyolefins are usually used by applying them in the form of a solution in an organic solvent or a dispersion in water. In terms of safety and hygiene and environmental pollution, aqueous dispersions are usually preferably used.
[0004] Patent Document 1 describes a resin dispersion in which a polymer in which a hydrophilic polymer is bound to an acid-modified polyolefin is dispersed in an aqueous medium, and the resin dispersion can be used as a coating material, primer, or adhesive for polyolefins, and describes a laminate as a coated product. The method described in Patent Document 1 does not mention the control of coating film properties such as the elastic modulus of the dried coating film, and low-temperature heat sealability remains an issue.
[0005] On the other hand, Patent Document 2 describes the use of a resin dispersion of an olefin polymer and an acrylic polymer as a heat sealant. The method described in Patent Document 2 describes that the heat sealant may be used for a polypropylene substrate, but does not mention the effect of adhesion to a non-polar polypropylene substrate as a specific example, and the adhesion to a polypropylene substrate is unclear, leaving issues. Patent Document 3 describes that the use of a resin dispersion of an olefin polymer and an acrylic polymer improves adhesion to a polypropylene substrate, but does not describe specific effects on the coating film properties such as the elastic modulus of the dried coating film when heat sealing is performed at low temperatures, leaving issues with low-temperature heat sealability. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2007-270122 A [Patent Document 2] JP 2001-179909 A [Patent Document 3] JP 2018-104620 A Summary of the Invention [Problem to be solved by the invention]
[0007] An object of the present invention is to provide an adhesive using an aqueous resin dispersion having excellent adhesion, which has excellent low-temperature heat sealability to polyolefin substrates and can be easily bonded to polyolefin substrates by heating at a low temperature for a short period of time, and a laminate containing a dried product of the adhesive. [Means for solving the problem]
[0008] That is, the present invention relates to the following items [1] to
[39] . [1] An aqueous resin dispersion C comprising, in the same particle, a polymer A having a constituent unit derived from an olefin-based monomer and a polymer B having a constituent unit derived from a radically polymerizable monomer, wherein the aqueous resin dispersion C is dried at 80°C for 30 minutes to give a coating film having an elastic modulus of more than 0 MPa and not more than 35 MPa. [2] The aqueous resin dispersion C according to [1], wherein the coating film obtained by drying the aqueous resin dispersion C at 80° C. for 30 minutes has a breaking elongation of 100% or more and 3000% or less. [3] The aqueous resin dispersion C according to [1] or [2], wherein the coating film obtained by drying the aqueous resin dispersion C at 80° C. for 30 minutes has a breaking elongation of 800% or more and 3000% or less. [4] The aqueous resin dispersion C according to any one of [1] to [3], wherein the mass ratio of structural units derived from aromatic monomers to all structural units of the polymer B is from 1.0 mass % to 30.0 mass %. [5] The aqueous resin dispersion C according to any one of [1] to [4], wherein the polymer A includes at least one selected from the group consisting of a polymer A1 having a structural unit derived from an olefin-based monomer having no reactive group, and a modified polymer A2 having a structural unit derived from an olefin-based monomer and a reactive group. [6] The polymer A includes the polymer A1, and the polymer A1 preferably includes at least one selected from the group consisting of a homopolymer of ethylene or propylene, a copolymer of ethylene and propylene, a copolymer of at least one selected from the group consisting of ethylene and propylene and at least one selected from the group consisting of 1-butene, 1-pentene, 1-hexene, 1-heptene, 1-octene, cyclopentene, cyclohexene, and norbornene (hereinafter also referred to as "α-olefin monomer"). A copolymer of at least one selected from the α-olefin monomer and at least one selected from the group consisting of vinyl acetate, acrylic acid ester, and methacrylic acid ester, a copolymer of at least one selected from the α-olefin monomer and an aromatic vinyl monomer and a hydrogenated product thereof, a conjugated diene block copolymer and a hydrogenated product thereof; polyethylene, polypropylene, an ethylene-butene copolymer, an ethylene-propylene copolymer, a propylene-butene copolymer, a propylene-hexene copolymer, a chlorinated The aqueous resin dispersion C according to [5] preferably contains at least one selected from the group consisting of polyethylene, chlorinated polypropylene, chlorinated ethylene-propylene copolymer, chlorinated propylene-butene copolymer, ethylene-vinyl acetate copolymer, hydrogenated styrene-butadiene-styrene block copolymer (SEBS), and hydrogenated styrene-isoprene-styrene block copolymer (SEPS); more preferably contains at least one selected from the group consisting of propylene homopolymer, copolymer of propylene and other α-olefin, and chlorinated polymers thereof; more preferably contains propylene homopolymer, ethylene-propylene copolymer, propylene-butene copolymer, chlorinated polypropylene, chlorinated ethylene-propylene copolymer, or chlorinated propylene-butene copolymer, and particularly preferably contains at least one selected from the group consisting of chlorine-free propylene homopolymer, ethylene-propylene copolymer, propylene-butene copolymer, and ethylene-propylene-butene copolymer. [7] The aqueous resin dispersion C according to any one of [1] to [6], wherein the weight average molecular weight (Mw) of the polymer A is preferably from 5,000 to 500,000, more preferably from 10,000 to 500,000, further preferably from 50,000 to 300,000, and particularly preferably from 100,000 to 300,000. [8] The aqueous resin dispersion C according to any one of [1] to [7], wherein the molecular weight distribution (Mw / Mn) of the polymer A is preferably from 0.5 to 5.0, more preferably from 1.0 to 4.0, and even more preferably from 1.5 to 3.0. [9] The aqueous resin dispersion C according to any one of [1] to [8], wherein the glass transition temperature of the polymer B is preferably from -80°C to 20°C, more preferably from -80°C to 10°C, further preferably from -70°C to 5°C, and particularly preferably from -60°C to less than -3°C.
[10] The radical polymerizable monomer preferably includes a vinyl monomer; more preferably includes at least one selected from the group consisting of (meth)acrylic monomers, aromatic monomers, amide monomers, (meth)acrylonitrile, vinyl acetate, vinyl propionate, and vinyl versatate; and further preferably includes at least one selected from the group consisting of (meth)acrylic acid, (meth)acrylic acid esters, styrene, and α-methylstyrene; and further preferably includes at least one selected from the group consisting of methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, t-butyl (meth)acrylate, hexyl (meth)acrylate, cyclohexyl (meth)acrylate, octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, nonyl (meth)acrylate, lauryl (meth)acrylate, stearyl (meth)acrylate, (meth)acrylic acid, The aqueous resin dispersion C according to any one of [1] to [9], particularly preferably contains at least one selected from the group consisting of benzyl acrylate, dimethylaminoethyl (meth)acrylate, diethylaminoethyl (meth)acrylate, 2-aminoethyl (meth)acrylate, glycidyl (meth)acrylate, 2-methoxyethyl (meth)acrylate, 3-methoxypropyl (meth)acrylate, an adduct of (meth)acrylic acid and polyethylene oxide, trifluoromethylmethyl (meth)acrylate, 2-trifluoromethylethyl (meth)acrylate, 2-perfluoroethylethyl (meth)acrylate, styrene, and α-methylstyrene; and most preferably contains at least one selected from the group consisting of isobutyl (meth)acrylate, butyl (meth)acrylate, t-butyl (meth)acrylate, cyclohexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, glycidyl (meth)acrylate, and styrene.
[11] The aqueous resin dispersion C according to any one of [1] to
[10] , wherein the radical polymerizable monomer comprises a vinyl monomer having at least one selected from the group consisting of a hydroxyl group and an epoxy group, and the mass proportion of the structural units derived from the vinyl monomer is preferably from 1.0 mass% to 30 mass%, more preferably from 1.5 mass% to 20 mass%, further preferably from 2.0 mass% to 15 mass%, and particularly preferably from 5.0 mass% to 10.0 mass%, relative to the total mass of the structural units constituting the polymer B.
[12] The aqueous resin dispersion C according to any one of [1] to
[11] , wherein the radical polymerizable monomer comprises an aromatic monomer, and the mass ratio of the structural units derived from the aromatic monomer is preferably from 5.0 mass% to 80 mass% relative to the total mass of the structural units constituting the polymer B, more preferably from 8.0 mass% to 70 mass%; further preferably from 10.0 mass% to 65 mass%; and particularly preferably from 12.0 mass% to 60 mass%.
[13] The aqueous resin dispersion C according to any one of [1] to
[12] , wherein the mass ratio of the polymer A to the total mass of the polymer A and the polymer B is preferably 30 mass% or more and 90 mass% or less, more preferably 50 mass% or more and 80 mass% or less, still more preferably 60 mass% or more and 75 mass% or less, and particularly preferably 65 mass% or more and 70 mass% or less.
[14] The aqueous resin dispersion C according to any one of [1] to
[13] , wherein the mass ratio of the polymer B to the total mass of the polymer A and the polymer B is preferably 10 mass% or more and 70 mass% or less, more preferably 30 mass% or more and 60 mass% or less, and even more preferably 35 mass% or more and 55 mass% or less.
[15] The aqueous resin dispersion C according to any one of [1] to
[14] , wherein the mass ratio represented by [the mass of the polymer A]:[the mass of the polymer B] is preferably from 30:70 to 90:10, more preferably from 40:60 to 80:20, and even more preferably from 50:50 to 70:30.
[16] The aqueous resin dispersion C according to any one of [1] to
[15] , wherein the particles essentially consist of the polymer A and the polymer B.
[17] The aqueous resin dispersion C according to any one of [1] to
[16] , wherein a coating film formed by drying the aqueous resin dispersion C at 80° C. for 30 minutes has an elastic modulus of more than 0 MPa and not more than 35 MPa, preferably from 5 MPa to 35 MPa, and more preferably from 10 MPa to 25 MPa.
[18] The aqueous resin dispersion C according to any one of [1] to
[17] , wherein the breaking elongation of a coating film formed by drying the aqueous resin dispersion C at 80° C. for 30 minutes is preferably 100% or more and 3000% or less, more preferably 800% or more and 3000% or less, further preferably 1000% or more and 2500% or less, and particularly preferably 1500% or more and 2000% or less.
[19] The aqueous resin dispersion C according to any one of [1] to
[18] , wherein the average particle size of the particles is preferably more than 0 μm and not more than 0.5 μm, more preferably from 0.05 μm to 0.3 μm, and even more preferably from 0.1 μm to 0.2 μm.
[20] The aqueous resin dispersion C according to any one of [1] to
[19] , which is obtained by polymerizing the radical polymerizable monomer in a dispersion of the polymer A to form the polymer B.
[21] The aqueous resin dispersion C according to any one of [1] to
[20] , wherein a laminate containing a dried product of the aqueous resin dispersion C is formed from a composition D containing the aqueous resin dispersion C, a test piece having a width of 15 mm is taken from the laminate, and an interface is peeled from an end of the test piece by 90-degree peeling using a tensile tester. The peel strength of the composition D (measurement conditions: in an atmosphere of 23°C and 65% RH, tensile speed of 50 mm / min) is preferably 1.00 N / 15 mm or more and 10.00 N / 15 mm or less, more preferably 2.00 N / 15 mm or more and 8.00 N / 15 mm or less, further preferably 3.00 N / 15 mm or more and 7.00 N / 15 mm or less, and particularly preferably 4.00 N / 15 mm or more and 6.00 N / 15 mm or less.
[0009]
[22] A composition D comprising the aqueous resin dispersion C according to any one of [1] to
[21] .
[23] Composition D according to
[22] , wherein composition D is a heat seal adhesive for polyolefin substrates.
[24] Composition D according to
[22] or
[23] , wherein the mass ratio of the polymer A to the total mass of the polymer A and the polymer B is 30 mass% or more.
[25] Composition D according to any one of
[22] to
[24] , wherein the olefin monomer comprises propylene.
[26] Composition D described in any one of
[22] to
[25] , wherein the glass transition temperature of the polymer B is −80° C. or higher and 20° C. or lower.
[27] Composition D described in any one of
[22] to
[26] , wherein the glass transition temperature of the polymer B is −80° C. or higher and lower than −3° C.
[28] Composition D according to any one of
[22] to
[27] , wherein the mass ratio of the aqueous resin dispersion C to the total mass of the composition D is preferably 80 mass% or more and 100 mass% or less, and more preferably 90 mass% or more and 100 mass% or less.
[0010]
[29] A laminate comprising a dried product of composition D according to any one of
[22] to
[28] .
[30] The laminate according to
[29] , wherein the dried product is a layer consisting of a dried product of the composition D.
[31] The laminate according to
[29] or
[30] , comprising a polypropylene base layer 1, a layer 2 made of a dried product of composition D, and at least one layer 3 selected from the group consisting of a metal foil, an inorganic vapor deposition film layer, and a thermoplastic resin layer, laminated in this order.
[32] The laminate according to
[30] or
[31] , wherein the thickness of the layer made of the dried product of composition D is preferably 10 μm or more and 60 μm or less, and more preferably 20 μm or more and 50 μm or less.
[33] The laminate according to
[31] or
[32] , wherein the thickness of the layer 1 is preferably 10 μm or more and 60 μm or less, and more preferably 20 μm or more and 50 μm or less.
[34] The laminate according to any one of
[31] to
[33] , wherein the thickness of the layer 3 is preferably 10 μm or more and 60 μm or less, and more preferably 20 μm or more and 50 μm or less.
[35] The layer 3 is a thermoplastic resin layer, and the thermoplastic resin layer is made of a material selected from the group consisting of polyethylene resins, polypropylene resins, cyclic polyolefin resins, fluorine-based resins, polystyrene resins, acrylonitrile-styrene copolymers (AS resins), acrylonitrile-butadiene-styrene copolymers (ABS resins), polyvinyl chloride resins, fluorine-based resins, poly(meth)acrylic resins, polycarbonate resins, polyester resins such as polyethylene terephthalate and polyethylene naphthalate, polyamide resins such as various nylons, polyimide resins, and polyamide-imide resins. The laminate according to any one of
[31] to
[34] , preferably a film or sheet containing at least one resin selected from the group consisting of polyarylphthalate-based resins, silicone-based resins, polysulfone-based resins, polyphenylene sulfide-based resins, polyethersulfone-based resins, polyurethane-based resins, acetal-based resins, cellulose-based resins, and polyvinyl alcohol resins; and more preferably a film or sheet containing at least one resin selected from the group consisting of polypropylene-based resins, polyester-based resins, and polyamide-based resins.
[36] The laminate according to any one of
[31] to
[34] , wherein Layer 3 is a metal foil or an inorganic vapor deposition film layer, and the metal foil or the inorganic vapor deposition film layer is preferably at least one selected from the group consisting of a soft metal foil such as an aluminum foil, an aluminum vapor deposition layer, a silica vapor deposition layer, an alumina vapor deposition layer, and an inorganic vapor deposition layer of silica-alumina binary vapor deposition; more preferably at least one selected from the group consisting of an aluminum foil, and an aluminum vapor deposition film.
[37] A food packaging material comprising composition D described in
[23] .
[38] A method for producing the aqueous resin dispersion C according to any one of [1] to
[21] , comprising a step of polymerizing a radically polymerizable monomer in the dispersion of the polymer A.
[39] The method for producing the aqueous resin dispersion C according to
[38] , comprising: supplying and polymerizing the radical polymerizable monomer in an amount of 80 to 100% by weight based on the total amount of the radical polymerizable monomer in the polymerization step; and supplying and polymerizing the remaining amount of the radical polymerizable monomer during the polymerization. Effect of the Invention
[0011] According to the present invention, it is possible to provide an adhesive using an aqueous resin dispersion having excellent adhesion, which has excellent low-temperature heat sealability to polyolefin substrates and can be easily adhered to a polyolefin substrate by heating at a low temperature for a short period of time, and a laminate containing a dried product of the adhesive. [Brief description of the drawings]
[0012] [Figure 1] FIG. 2 is an explanatory diagram showing an example of a laminate; [Diagram 2] FIG. 1 is an explanatory diagram showing an example of a food packaging material. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] In this specification, "~" means including the numbers before and after it. In addition, in this specification, "dispersion" means a state in which dispersed particles are extremely small and dispersed as monomolecules, and a state that can be said to be substantially dissolved. Furthermore, in the present invention, "(meth)acrylic" is a general term for acrylic and methacrylic.
[0014] The aqueous resin dispersion C of the present invention is an aqueous resin dispersion C containing a polymer A having a structural unit derived from an olefin-based monomer and a polymer B having a structural unit derived from a radically polymerizable monomer within the same particle. Each component is described below.
[0015] [Polymer A having structural units derived from olefin monomer] A polymer having a structural unit derived from an olefin-based monomer means a polymer made from an olefin as a raw material monomer, and means a polymer A (hereinafter sometimes referred to as "polymer A") having a structural unit derived from an olefin-based monomer, such as an olefin homopolymer or copolymer.
[0016] Examples of the polymer A having a structural unit derived from an olefin-based monomer include a polymer A1 having a structural unit derived from an olefin-based monomer having no reactive group (hereinafter, sometimes referred to as "polymer A1"), and a modified polymer A2 having a structural unit derived from a reactive group and an olefin-based monomer (hereinafter, sometimes referred to as "polymer A2").
[0017] A preferred embodiment of the polymer A is a propylene-based polymer that satisfies the following (1) and (2). (1) In terms of obtaining good adhesion to a propylene substrate, the propylene content of the polymer A is preferably 50 mol % or more, more preferably 60 mol % or more, and even more preferably 70 mol % or more. (2) In order to obtain good adhesion during low-temperature heat sealing at 120° C. or less, the melting point [Tm] of the polymer A is preferably 120° C. or less, more preferably 100° C. or less, and even more preferably 90° C. or less. The lower limit of Tm is preferably 60° C. or more in terms of excellent blocking properties.
[0018] [Polymer A1 having structural units derived from olefin monomer having no reactive group] As the polymer A1, known olefin polymers and olefin copolymers can be used. The polymer A1 is not particularly limited, but examples thereof include homopolymers of ethylene or propylene; copolymers of ethylene and propylene; copolymers of at least one selected from the group consisting of ethylene and propylene with other monomers, such as 1-butene, 1-pentene, 1-hexene, 1-heptene, 1-octene, cyclopentene, cyclohexene, and norbornene, and α-olefin monomers having 2 or more carbon atoms, or copolymers of two or more of the α-olefin monomers; copolymers of the α-olefin monomers with monomers such as vinyl acetate, acrylic acid esters, and methacrylic acid esters; copolymers of the α-olefin monomers with monomers such as aromatic vinyl monomers, or hydrogenated products thereof; conjugated diene block copolymers or hydrogenated products thereof, and the like.
[0019] The α-olefin monomer is preferably an α-olefin monomer having 2 to 4 carbon atoms, since the polymer A1 having a structural unit derived from an olefin-based monomer is soluble in a solvent and can easily react. The various copolymers may be at least one selected from the group consisting of random copolymers and block copolymers. As the various copolymers, chlorinated polyolefins obtained by chlorinating polyolefins may also be used. In order to improve the solubility of the olefin polymer A1 in a solvent, the chlorination degree of the chlorinated polyolefin is preferably 5% by weight or more, more preferably 10% by weight or more, based on the total mass of the polyolefin. Also, it is preferably 40% by weight or less, more preferably 30% by weight or less.
[0020] Specific examples of the polymer A1 include polyethylene, polypropylene, ethylene-butene copolymer, ethylene-propylene copolymer, propylene-butene copolymer, propylene-hexene copolymer, chlorinated polyethylene, chlorinated polypropylene, chlorinated ethylene-propylene copolymer, chlorinated propylene-butene copolymer, ethylene-vinyl acetate copolymer, hydrogenated styrene-butadiene-styrene block copolymer (SEBS), and hydrogenated styrene-isoprene-styrene block copolymer (SEPS).
[0021] In terms of achieving good adhesion to a propylene substrate, the polymer A1 is preferably a propylene homopolymer, a copolymer of propylene and another α-olefin, or a chlorinated polymer thereof, more preferably a propylene homopolymer, an ethylene-propylene copolymer, a propylene-butene copolymer, a chlorinated polypropylene, a chlorinated ethylene-propylene copolymer, or a chlorinated propylene-butene copolymer, and even more preferably a chlorine-free propylene homopolymer, an ethylene-propylene copolymer, a propylene-butene copolymer, or an ethylene-propylene-butene copolymer.
[0022] The polymer A1 may be used alone or in combination of two or more kinds.
[0023] The polymer A1 is preferably a propylene-based polymer having a propylene-derived structural unit as a structural unit thereof. That is, the olefin-based monomer preferably contains propylene. When the olefin-based monomer contains propylene, the adhesion to the polypropylene substrate tends to increase. The ratio of the propylene-derived structural units to the total structural units of the propylene-based polymer is preferably 50 mol% or more, more preferably 60 mol% or more, and even more preferably 70 mol% or more. Within the above range, the higher the ratio of the propylene-derived structural units, the higher the adhesion to the polypropylene substrate tends to increase.
[0024] The weight average molecular weight Mw of the polymer A1 can be measured by GPC (Gel Permeation Chromatography) and converted by the calibration curve of each polyolefin to obtain Mw. The weight average molecular weight Mw of the polymer A1 is preferably 5,000 or more, more preferably 10,000 or more, even more preferably 50,000 or more, and particularly preferably 100,000 or more. Also, it is preferably 500,000 or less, and more preferably 300,000 or less. Within the above range, the higher the Mw, the less sticky the resin tends to be and the more adhesive the resin to the substrate tends to be. Also, within the above range, the lower the Mw, the lower the viscosity, and the easier it tends to be to prepare the aqueous resin dispersion.
[0025] The weight average molecular weight Mw can be measured by GPC using a commercially available GPC device and a solvent such as orthodichlorobenzene, according to a conventional method.
[0026] The melting point Tm of the polymer A1 is preferably 120° C. or lower, more preferably 100° C. or lower, and even more preferably 90° C. or lower. The melting point Tm of the polymer A1 is preferably 50° C. or higher. Within the above range, the higher the melting point, the better the blocking property tends to be. Furthermore, the lower the melting point, the better the low-temperature heat sealability tends to be.
[0027] The method for producing the polymer A1 is not particularly limited as long as it can produce a polymer that satisfies the requirements of the present invention, and any method may be used. For example, radical polymerization, cationic polymerization, anionic polymerization, coordination polymerization, etc. may be used, and each method may be a living polymerization method.
[0028] In the case of coordination polymerization, for example, a method of polymerization using a Ziegler-Natta catalyst or a method of polymerization using a single-site catalyst can be used. Among these, a method of polymerization using a single-site catalyst is preferred because it is possible to sharpen the molecular weight distribution and stereoregularity distribution by designing the ligand.
[0029] As the single-site catalyst, for example, a metallocene catalyst or a Brookhart catalyst can be used. As the metallocene catalyst, a suitable catalyst such as C1 symmetric type, C2 symmetric type, C2V symmetric type, or CS symmetric type can be selected according to the stereoregularity of the polyolefin to be polymerized.
[0030] The method for producing the polymer A1 can be carried out in any form of polymerization, such as solution polymerization, slurry polymerization, bulk polymerization, and gas phase polymerization. Examples of the solvent in the case of solution polymerization and slurry polymerization include aromatic hydrocarbons such as toluene and xylene; aliphatic hydrocarbons such as hexane, heptane, and octane; alicyclic hydrocarbons such as cyclohexane and methylcyclohexane; halogenated hydrocarbons, esters, ketones, and ethers. Among them, aromatic hydrocarbons, aliphatic hydrocarbons, and alicyclic hydrocarbons are preferred in terms of easily dissolving the polymer A1, and toluene, xylene, heptane, and cyclohexane are more preferred. These may be used alone or in combination of two or more. The molecular structure of the polymer A1 may be linear or branched.
[0031] [Modified polymer A2 having a reactive group and a structural unit derived from an olefin monomer] Examples of the polymer A2 include a copolymer A2a obtained by copolymerizing an olefin with an unsaturated compound having a reactive group during modification polymerization, and a graft polymer A2b obtained by graft polymerizing a radically polymerizable unsaturated compound having a reactive group onto a polymer having a structural unit derived from an olefin monomer.
[0032] The copolymer A2a is obtained by copolymerizing an olefin and an unsaturated compound having a reactive group, and is a copolymer in which the unsaturated compound having a reactive group is introduced into the main chain. Examples of the copolymer A2a include copolymers of α-olefins such as ethylene, propylene, and butene with α,β-unsaturated carboxylic acids or their anhydrides such as acrylic acid and maleic anhydride. The copolymer A2a may be an ethylene-acrylic acid copolymer, an ethylene-acrylic acid ester-maleic anhydride copolymer, or the like. These may be used alone or in combination of two or more. The copolymer A2a may be produced by the same method as described for the polymer A1.
[0033] The graft polymer A2b can be obtained by graft polymerizing a radically polymerizable unsaturated compound having a reactive group to a polymer having a structural unit derived from an olefin monomer. Examples of the reactive group include a carboxyl group, an amino group, an epoxy group, an isocyanate group, a sulfonyl group, and a hydroxyl group. Among these, the reactive group is preferably a carboxyl group or an anhydride thereof, since the reactive group has excellent reactivity. Examples of the graft polymer A2b include a polymer obtained by graft polymerizing a polyolefin such as polyethylene or polypropylene with (meth)acrylic acid, fumaric acid, maleic acid, itaconic acid or anhydrides thereof, crotonic acid, or the like. These may be used alone or in combination of two or more.
[0034] The polymer A1 can be used as the polymer having a structural unit derived from an olefin monomer that can be used for the graft polymer A2b. Examples of the graft polymer A2b include maleic anhydride-modified polypropylene and its chlorine derivative, maleic anhydride-modified ethylene-propylene copolymer and its chlorine derivative, maleic anhydride-modified propylene-butene copolymer, acrylic acid-modified polypropylene and its chlorine derivative, acrylic acid-modified ethylene-propylene copolymer and its chlorine derivative, acrylic acid-modified propylene-butene copolymer, etc. These may be used alone or in combination of two or more.
[0035] The radical polymerization initiator used in the production of the graft polymer A2b can be appropriately selected from ordinary radical polymerization initiators, and examples thereof include organic peroxides and azonitriles. Examples of the organic peroxides include peroxyketals such as di(t-butylperoxy)cyclohexane; hydroperoxides such as cumene hydroperoxide; dialkyl peroxides such as di(t-butyl)peroxide; diacyl peroxides such as benzoyl peroxide; and peroxyesters such as t-butylperoxyisopropyl monocarbonate. Examples of the azonitriles include azobisbutyronitrile and azobisisopropylnitrile. Among these, benzoyl peroxide and t-butylperoxyisopropyl monocarbonate are preferred because of their strong hydrogen abstraction power and excellent graft reaction. These may be used alone or in combination of two or more.
[0036] The ratio of the radical polymerization initiator to all the constituent units of the graft polymer A2b is preferably radical polymerization initiator: all the constituent units of the graft polymer A2b = 1:100 to 2:1 (molar ratio), more preferably 1:20 to 1:1 (molar ratio). Within the above range, bonding between the graft copolymers can be suppressed. The reaction temperature is preferably 50°C or higher, more preferably 80 to 200°C. Within the above range, the graft reaction proceeds due to the hydrogen abstraction power of the radical polymerization initiator. The reaction time is usually about 2 to 20 hours.
[0037] The method for producing the polymer A2b is not particularly limited, and may be any method. The method for producing the polymer A2b includes a method of reacting by heating and stirring in a solution, a method of reacting by melting and heating and stirring without a solvent, and a method of reacting by heating and kneading in an extruder. The solvent for producing the polymer A2b in a solution may be the same as that described for the polymer A1.
[0038] The content of the reactive group in the polymer A2 is preferably 0.01 mmol / g or more, more preferably 0.05 mmol / g or more, and even more preferably 0.1 mmol / g or more per 1 g of the polymer A2. Also, it is preferably 1 mmol / g or less, more preferably 0.5 mmol / g or less, and even more preferably 0.3 mmol / g or less. Within the above range, the higher the content, the more hydrophilic the dispersed particle size tends to be smaller, and the lower the content, the more adhesive the polypropylene substrate tends to be.
[0039] [Dispersion of Polymer A] Examples of a method for producing a dispersion of the polymer A include a method of dispersing the polymer A by adding a surfactant to the polymer A, a method of dispersing a graft copolymer by using a graft copolymer in which a hydrophilic polymer is graft-bonded to the polymer A, and a method of dispersing the polymer A2 by neutralizing the acidic group with a basic compound when the reactive group of the polymer A2 is an acidic group such as a carboxyl group or an anhydride thereof, or a sulfonyl group.
[0040] The hydrophilic polymer used in the dispersion of polymer A means a polymer having an insoluble content of 1% by weight or less when dissolved in water at 25° C. at a concentration of 10% by weight. The hydrophilic polymer can be used without any particular limitation as long as it does not significantly impair the effects of the present invention, and synthetic polymers, semi-synthetic polymers, natural polymers, etc. can be used. In terms of excellent mechanical stability of the polyolefin dispersion, the number average molecular weight Mn of the hydrophilic polymer is preferably 300 or more.
[0041] Examples of the basic compound used in the dispersion of the polymer A include inorganic bases such as sodium hydroxide and potassium hydroxide; and organic bases such as ammonia, triethylamine, diethylamine, ethanolamine, dimethylethanolamine, 2-methyl-2-amino-propanol, triethanolamine, morpholine, and pyridine. The neutralization rate by the basic compound is not particularly limited as long as it is within a range in which dispersibility in water can be obtained, but is preferably 1 to 100 mol % relative to the acidic group, and more preferably 50 mol % or more. Within the above range, the higher the neutralization rate, the better the dispersibility in water.
[0042] In the present invention, the dispersion means a state in which the dispersed particles are very small and dispersed as monomolecules, and includes a state that can be said to be substantially dissolved. Therefore, the lower limit of the average particle size of the dispersion may be 0 μm. The average particle size of the dispersion of the polymer A used in the present invention is preferably 0.5 μm or less, more preferably 0.3 μm or less, and even more preferably 0.2 μm or less. The average particle size of the dispersion of the polymer A is preferably 0 μm or more. If it is within the above range, the dispersion stability is improved and aggregation is less likely to occur. The dispersed particle size can be measured by a dynamic light scattering method, a laser Doppler method, or the like.
[0043] The solid content of the dispersion of polymer A is preferably 5% by weight or more, more preferably 10% by weight or more, and even more preferably 20% by weight or more, based on the total weight of the dispersion of polymer A. Also, it is preferably 70% by weight or less, more preferably 60% by weight or less, and even more preferably 50% by weight or less. Within the above range, the lower the solid content, the lower the viscosity and the more excellent the polymerizability with the radical polymerizable monomer tends to be. Also, the higher the solid content, the less energy is required for drying, and the more excellent the drying property tends to be.
[0044] The ratio of the solvent other than water in the dispersion of the polymer A is preferably 50% by weight or less, more preferably 20% by weight or less, and even more preferably 10% by weight or less, based on the total weight of the dispersion of the polymer A. Within the above range, the less the solvent, the better the storage stability tends to be. In terms of improving the storage stability of the aqueous resin dispersion C, the solvent is preferably a solvent that dissolves in water at 1% by weight or more, and more preferably a solvent that dissolves in water at 5% by weight or more. Examples of the solvent other than water include methyl ethyl ketone, cyclohexanone, n-propanol, isopropanol, n-butanol, isobutanol, t-butanol, cyclohexanol, tetrahydrofuran, 2-methoxyethanol, 2-ethoxyethanol, 2-butoxyethanol, 2-methoxypropanol, and 2-ethoxypropanol. These may be used alone or in combination of two or more.
[0045] Examples of the dispersion of polymer A that can be used include Auroren and Superchron manufactured by Nippon Paper Industries Co., Ltd., Hardlen manufactured by Toyobo Co., Ltd., Aptlock manufactured by Mitsubishi Chemical Corporation, and Arrowbase manufactured by Unitika Ltd. Among these, Auroren, Hardlen, Aptlock, and Arrowbase are preferred because they do not contain chlorine, and Aptlock is more preferred.
[0046] [Polymer B having structural units derived from radically polymerizable monomers] The glass transition temperature of polymer B is preferably 20° C. or lower, more preferably 10° C. or lower, even more preferably 5° C. or lower, and particularly preferably less than −3° C. If the glass transition temperature of polymer B is 20° C. or lower, the flexibility and film-forming property of the coating film are improved, and the low-temperature heat sealability is improved. In addition, from the viewpoint of improving the blocking property of the coating film, the glass transition temperature of acrylic polymer B is preferably −80° C. or higher, more preferably −70° C. or higher, and even more preferably −60° C. or higher. That is, the glass transition temperature of polymer B is preferably −80° C. or higher and 20° C. or lower, and more preferably −80° C. or higher and less than −3° C.
[0047] The glass transition temperature of the polymer B means a value calculated by the Fox formula represented by the following formula (i).
[0048] 1 / (273+Tg)=Σ(Wi / (273+Tgi))...Equation (i) (In formula (i), Wi represents the mass fraction of monomer i, and Tgi represents the Tg (°C) of a homopolymer of monomer i. Here, the glass transition temperature of the homopolymer of each monomer can be the value described in POLYMER HANDBOOK Fourth Edition, John Wiley & Sons, Inc. (1999).)
[0049] The radical polymerizable monomer is preferably a vinyl monomer because of its excellent polymerizability. Examples of the vinyl monomer include (meth)acrylic monomers such as (meth)acrylic acid and (meth)acrylic acid esters; aromatic monomers such as styrene and α-methylstyrene; amide monomers such as (meth)acrylamide and dimethyl(meth)acrylamide; (meth)acrylonitrile, vinyl acetate, vinyl propionate, and vinyl versatate. The vinyl monomer can be used without any particular limitation as long as it does not significantly impair the effects of the present invention.
[0050] Among these, (meth)acrylic acid esters are preferred in terms of weather resistance and solvent resistance of the coating film. Specific examples of the (meth)acrylic acid esters include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, t-butyl (meth)acrylate, hexyl (meth)acrylate, cyclohexyl (meth)acrylate, octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, nonyl (meth)acrylate, lauryl (meth)acrylate, stearyl (meth)acrylate, (meth)acrylic acid esters having an aryl group or aralkyl group having 6 to 12 carbon atoms, such as (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, t-butyl (meth)acrylate, hexyl (meth)acrylate, cyclohexyl (meth)acrylate, octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, nonyl (meth)acrylate, lauryl (meth)acrylate, stearyl (meth)acrylate, and ... ethyl (meth)acrylate, ethyl (meth)acrylate, ethyl (meth)acrylate, ethyl (meth) p) Benzyl acrylate, etc.; dimethylaminoethyl (meth)acrylate, diethylaminoethyl (meth)acrylate, 2-aminoethyl (meth)acrylate, glycidyl (meth)acrylate, 2-methoxyethyl (meth)acrylate, 3-methoxypropyl (meth)acrylate, adducts of (meth)acrylic acid and polyethylene oxide, etc.; (meth)acrylic acid esters having an alkyl group having 1 to 20 carbon atoms and a fluorine atom, such as trifluoromethylmethyl (meth)acrylate, 2-trifluoromethylethyl (meth)acrylate, and 2-perfluoroethylethyl (meth)acrylate.
[0051] Among these, isobutyl (meth)acrylate, butyl (meth)acrylate, t-butyl (meth)acrylate, cyclohexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, and styrene are preferred from the viewpoint of adhesion to the propylene substrate.
[0052] In order to improve adhesion of the cured product layer 2 of the composition to the polypropylene base layer 1 and to at least one layer 3 selected from the group consisting of a metal foil, an inorganic vapor deposition film layer, and a thermoplastic resin, it is preferable that the polymer B contains 1.0 mass % or more and 30.0 mass % or less of structural units derived from an aromatic monomer based on all structural units of the polymer B.
[0053] Specific examples of the aromatic monomers mentioned above include styrene, phenoxyethyl methacrylate, α-methylstyrene, vinylnaphthalene, vinylanthracene, vinylpyrene, vinylanisole, vinylbenzoic acid ester, acetylstyrene, etc. Among these, styrene is preferred from the viewpoint of polymerizability.
[0054] When the aqueous resin dispersion C is mixed with a crosslinking agent such as a melamine resin or an isocyanate to form a coating composition, the radical polymerizable monomer preferably contains a vinyl monomer having a hydroxyl group or a vinyl monomer having an epoxy group, because the coating film performance is improved. Examples of the vinyl monomer having a hydroxyl group include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate. Examples of the vinyl monomer having an epoxy group include glycidyl (meth)acrylate, 1,2-epoxy 4-vinylcyclohexane, and 4-(2,3-epoxypropoxy)butyl (meth)acrylate. The amount of the vinyl monomer having a hydroxyl group or an epoxy group used is preferably 30% by weight or less, more preferably 20% by weight or less, based on the total amount of the radical polymerizable monomer used. Within the above range, the adhesion to the polypropylene substrate tends to be good.
[0055] From the viewpoint of adhesion to the metal substrate, the radical polymerizable monomer preferably contains a vinyl monomer having a carboxylic acid group or a phosphoric acid group. Examples of the vinyl monomer having a carboxylic acid group include (meth)acrylic acid. The amount of the vinyl monomer having a carboxylic acid group used is preferably 10% by weight or less, more preferably 5% by weight or less, based on the total amount of the radical polymerizable monomer used. Within the above range, the adhesion to the metal substrate and the polypropylene substrate tends to be good.
[0056] The mass ratio of the polymer B to the total mass of the polymer A and the polymer B is preferably 10% by mass or more, and more preferably 30% by mass or more. Also, the mass ratio is preferably 70% by mass or less, and more preferably 50% by mass or less. When it is within the above range, the adhesion to the polypropylene substrate is excellent.
[0057] The mass ratio of the polymer A to the total mass of the polymer A and the polymer B is preferably 30 mass % or more, more preferably 50 mass % or more, and even more preferably 65 mass % or more. Within this range, the adhesion to the polypropylene substrate is excellent.
[0058] [Production method of polymer B] Examples of the method for producing the polymer B include a method for polymerizing the radical polymerizable monomer in a state where the radical polymerizable monomer is dissolved in a dispersion of the polymer A, a method for polymerizing the polymer in a dispersion in which both the polymer A and the radical polymerizable monomer are dispersed, and a method for emulsion polymerization using the radical polymerizable monomer and a surfactant.
[0059] The method for producing the polymer B may be any method as long as a radical polymerizable monomer is polymerized in a dispersion of the polymer A, and either bulk polymerization or dropwise polymerization may be used as long as the effects of the present invention are not significantly impaired. The bulk polymerization is a method of polymerizing the entire amount of radical polymerizable monomers by charging them into a reaction vessel at once. When bulk polymerization is adopted for the production method of the polymer B, for example, the entire amount of the radical polymerizable monomers is mixed into the dispersion of the polymer A, and then polymerization can be performed by adding a water-soluble initiator or a redox initiator containing an organic peroxide and a reducing agent such as sodium thiosulfate. The dropwise polymerization is a method of polymerizing the monomers while dropping them into a reaction vessel in small amounts. When dropwise polymerization is adopted for the production method of the polymer B, for example, polymerization can be performed while dropping the radical polymerizable monomers into the dispersion of the polymer A. From the viewpoints of polymerization stability and adhesion to a propylene substrate, it is preferable to adopt the bulk polymerization in the method for producing the polymer B, and it is more preferable that the bulk polymerization is carried out by supplying and polymerizing the radical polymerizable monomer in an amount of 80 to 100% by weight based on the total amount of the radical polymerizable monomer, and supplying and polymerizing the remaining amount of the radical polymerizable monomer during the polymerization.
[0060] From the viewpoints of the production efficiency of the polymer B and the storage stability of the aqueous resin dispersion C, it is preferable to carry out the polymerization using a surfactant for emulsion polymerization. The surfactant for emulsion polymerization may be any of various anionic, cationic, or nonionic surfactants having an HLB value of 8 or more, and may also be a so-called reactive surfactant having an ethylenically unsaturated bond in the surfactant component. Among these, it is preferable to use an anionic surfactant from the viewpoint of improving the storage stability of the resulting dispersion. The anionic surfactant is not particularly limited, but may be Adeka Reasoap SR manufactured by ADEKA CORPORATION, which is a reactive surfactant, or Neocol SW-C, Newcol 707SF, which is a non-reactive surfactant, or the like.
[0061] The amount of the surfactant for emulsion polymerization used is preferably 5 parts by weight or less, more preferably 3 parts by weight or less, based on 100 parts by weight of the radical polymerizable monomer. If it is within the above range, the water resistance tends to be excellent.
[0062] As the initiator used for polymerization, an initiator generally used for radical polymerization can be used. Examples of the initiator include persulfates such as potassium persulfate, sodium persulfate, and ammonium persulfate; oil-soluble azo compounds such as azobisisobutyronitrile, 2,2'-azobis(2-methylbutyronitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile), and 2-phenylazo-4-methoxy-2,4-dimethylvaleronitrile; 2,2'-azobis{2-methyl-N-[1,1-bis(hydroxymethyl)-2-hydroxyethyl]propionamide}, 2,2'-azobis{2-methyl-N-[2-(1-hydroxyethyl)]propionamide}, and 2,2'-azobis{2-methyl-N-[2-(1-hydroxybutyl)]propionamide}. water-soluble azo compounds such as 2,2'-azobis(2-methylpropynamidine) and its salts; 2,2'-azobis[N-(2-carboxyethyl)-2-methylpropionamidine]; organic peroxides such as benzoyl peroxide, cumene hydroperoxide, t-butyl hydroperoxide, t-butyl peroxy-2-ethylhexanoate, and t-butyl peroxyisobutyrate. These may be used alone or in combination of two or more.
[0063] From the viewpoint of the polymerization rate of the obtained polymer B, it is preferable to use, as the initiator, a reducing agent such as sodium bisulfite, ferrous sulfate, isoascorbate, or Rongalit in combination with a water-soluble polymerization catalyst.
[0064] The polymerization temperature is preferably 50° C. or higher in terms of the polymerization rate of the polymer B obtained. The polymerization time is preferably 30 minutes or longer. If the polymerization time is 30 minutes or longer, the radical polymerizable monomer is sufficiently polymerized, and the polymerization rate tends to improve. In addition, the polymerization time is preferably 3 hours or shorter. If the polymerization time is 3 hours or shorter, cullets are unlikely to be generated during polymerization, and production efficiency tends to improve.
[0065] In the polymerization, a known chain transfer agent such as n-dodecyl mercaptan, t-dodecyl mercaptan, or α-methylstyrene dimer may be used as a molecular weight regulator.
[0066] After the polymerization reaction is completed, the mixture is cooled and then filtered to prevent contamination with foreign matter or cullet when the aqueous resin dispersion C is taken out. A known method for filtering can be used, and a nylon mesh, a bag filter, filter paper, a metal mesh, or the like can be used.
[0067] [Aqueous resin dispersion C] The mass ratio of the polymer A and the polymer B having a constitutional unit derived from a radical polymerizable monomer in the aqueous resin dispersion C is preferably A:B=30:70 to 90:10. Within the above range, a method of polymerizing the polymer A in a state where the radical polymerizable monomer is dissolved in the dispersion, a method of polymerizing the polymer A in a dispersion in a state where both the polymer A and the radical polymerizable monomer are dispersed, or the like can be used, and the aqueous resin dispersion C can be produced by a commonly known production method within a range that does not significantly impair the effects of the present invention.
[0068] The elastic modulus of the coating film obtained by drying the aqueous resin dispersion C at 80° C. for 30 minutes is greater than 0 MPa and less than 35 MPa, preferably greater than 5 MPa and less than 35 MPa, and more preferably greater than 10 MPa and less than 25 MPa. If the elastic modulus of the coating film is greater than 35 MPa, the coating film tends to have low fluidity and poor heat sealability. If the elastic modulus is less than 0 MPa, the coating film tends to have tackiness and poor blocking properties. The coating film has a breaking elongation of preferably 100% or more and 3000% or less, more preferably 800% or more and 3000% or less, further preferably 1000% or more, and particularly preferably 1500% or more. If the coating has a breaking elongation of less than 100%, the coating becomes brittle and tends to have poor adhesion strength.
[0069] Examples of the method for producing the aqueous resin dispersion C include a method of polymerizing a radical polymerizable monomer in a dispersion of the polymer A, a method of dissolving the olefin polymer A and a radical polymerizable monomer, dispersing them, and polymerizing them. From the viewpoint of adhesion to a polypropylene substrate, it is preferable to polymerize a radical polymerizable monomer in a dispersion of the polymer A. The polymerization method of the radical polymerizable monomer in the production method of the aqueous resin dispersion C can be performed by the same polymerization method as in the production method of the polymer B.
[0070] [Composition D] Composition D of the present invention is preferably made from aqueous resin dispersion C as a raw material. The aqueous resin dispersion C can be used as it is as the composition D of the present invention. In order to improve the adhesive strength, water resistance, heat resistance, chemical resistance, wettability, and other properties of the composition D, other resins than the aqueous resin dispersion C may be contained as necessary. Examples of the other resins include additives and crosslinking agents.
[0071] Examples of the additives include polyvinyl acetate, ethylene-vinyl acetate copolymer, polyvinyl chloride, polyvinylidene chloride, styrene-butadiene resin, butadiene resin, poly(meth)acrylonitrile resin, (meth)acrylamide resin, polyester resin, nylon resin, urethane resin, phenol resin, silicone resin, epoxy resin, etc. The content of the other resin is preferably less than 50% by weight, more preferably less than 30% by weight, and even more preferably less than 20% by weight, based on the total weight of the aqueous resin dispersion C.
[0072] The crosslinking agent is not particularly limited, but may be a compound having a functional group of two or more functional groups. The crosslinking agent may be a polyfunctional epoxy compound, a polyfunctional isocyanate compound, a polyfunctional amine compound, a polyfunctional oxazoline compound, a hydrazine compound, etc. Among these, from the viewpoint of reactivity with the carboxyl group of the acid-modified polyolefin, a polyfunctional epoxy compound, a polyfunctional oxazoline compound, and a hydrazine compound are preferred.
[0073] Composition D of the present invention may or may not contain a film-forming agent, a wetting agent, etc., for the purpose of increasing the drying speed or obtaining a surface with a good finish. An organic solvent can be used as the film-forming agent or the wetting agent. Examples of the organic solvent include alcohols such as methanol, ethanol, isopropanol, etc.; ketones such as acetone, etc.; glycols such as ethylene glycol, propylene glycol, ethylene glycol monobutyl ether, diethylene glycol monobutyl ether, propylene glycol monomethyl ether, etc., and ethers thereof. Moreover, as the wetting agent, a siloxane-based wetting agent can also be used.
[0074] The composition D of the present invention preferably contains an aqueous resin dispersion C containing a polymer A having a structural unit derived from an olefin monomer and a polymer B having a structural unit derived from a radical polymerizable monomer in the same particle, and further contains the other resins as required. As a method for producing the composition D, a production method in which the above-mentioned components are mixed with a commonly used stirrer, etc., can be mentioned.
[0075] The composition D is preferably a heat seal adhesive for polyolefin substrates because it has excellent low-temperature heat seal adhesion to polyolefin substrates. By using the composition D as a heat seal adhesive for polyolefin substrates, the low-temperature heat sealability to polyolefin substrates is improved, and adhesion to polyolefin substrates tends to be easily improved by heating at low temperature for a short time.
[0076] [Laminate] The laminate of the present invention is preferably a laminate containing a dried product of the resin composition D. By containing the dried product of the resin composition D, the low-temperature heat sealability and adhesion to a polyolefin substrate are improved. In addition, the laminate of the present invention preferably comprises a polypropylene base layer 1, a layer 2 formed from a dried product of composition D (hereinafter also referred to as "cured layer 2 of composition D"), and at least one layer 3 selected from the group consisting of metal foil, an inorganic vapor deposition film layer, and a thermoplastic resin, laminated in this order.D Figure 1 shows a laminate 10 in which a polypropylene base layer 1, a cured layer 2 of composition D, and at least one layer 3 selected from the group consisting of metal foil, an inorganic vapor deposition film layer, and a thermoplastic resin are laminated in this order.
[0077] Examples of the polypropylene base layer 1 in the present invention include polypropylene resins such as polypropylene-based resins, acid-modified polypropylene, and polypropylene-α-olefin copolymers. Among these, from the viewpoint of protecting the contents as a packaging material, polypropylene-based resins, propylene-ethylene copolymer resins, and propylene-butene copolymer resins are preferred, and polypropylene-based resins are more preferred.
[0078] Examples of the polypropylene base layer 1 include polypropylene-based base materials such as oriented polypropylene (OPP), non-oriented polypropylene (CPP), aluminum-deposited polypropylene, and co-extruded film polypropylene. Among these, oriented polypropylene (OPP) is preferred because of its excellent transparency and strength.
[0079] [Layer 2 of hardened composition] The cured composition layer 2 may be formed from a dried product of composition D, and the amount of composition D used is preferably 0.01 to 20 g / m2, more preferably 0.1 to 10 g / m2, and even more preferably 0.3 to 5 g / m2, relative to the area of the adhesive surface. If the amount used is less than 0.01 g / m2, sufficient adhesion cannot be obtained, and if it exceeds 20 g / m2, it takes a long time to dry, which is economically disadvantageous.
[0080] The cured layer 2 of the composition may be formed from a dried product of the composition D, and may be dried using a safevent dryer or the like after applying the composition D to at least one layer 3 selected from the group consisting of a metal foil, an inorganic vapor deposition film layer, and a thermoplastic resin. The drying temperature is preferably 60 to 150°C. If the temperature is 60°C or higher, the composition D can be dried in a short time. If the temperature is 150°C or lower, the transparency of the composition D is excellent.
[0081] A known coating method can be used as the coating method. Examples of the coating method include gravure roll coating, reverse roll coating, wire bar coating, lip coating, air knife coating, curtain flow coating, spray coating, dip coating, brush coating, etc. By uniformly coating the composition D on the substrate surface by the coating method and subjecting it to a drying treatment or a heat treatment for drying, the cured layer 2 of the composition can be adhered to the layer 3 of a thermoplastic resin or the like.
[0082] In the present invention, the metal foil and inorganic vapor deposition film layer may be a soft metal foil such as aluminum foil, or an inorganic vapor deposition layer such as aluminum vapor deposition, silica vapor deposition, alumina vapor deposition, or silica-alumina binary vapor deposition, as a barrier layer having light-shielding and gas-barrier properties. Aluminum foil or aluminum vapor deposition film is preferred because it is inexpensive, has high barrier properties, and can provide light-shielding properties.
[0083] The aluminum foil layer constituting the laminate may be subjected to hydrothermal modification treatment on the surface in contact with the cured layer 2 of the composition in order to improve adhesion. Examples of treatment water used when subjecting the surface of the aluminum foil to hydrothermal modification treatment include tap water, deionized water, distilled water, and deionized distilled water. Among these, deionized distilled water is preferred. In the hydrothermal modification treatment of the surface of the aluminum foil, a film of various hydrated oxides is coated on the surface depending on the treatment temperature, forming a hydrothermal modification treatment layer. As the hydrothermal modification treatment, boehmite treatment (hydrothermal modification treatment) performed under normal pressure and at about 80 to 100°C is preferred.
[0084] As the thermoplastic resin layer, films or sheets of various resins such as polyethylene resins, polypropylene resins, cyclic polyolefin resins, fluorine resins, polystyrene resins, acrylonitrile-styrene copolymers (AS resins), acrylonitrile-butadiene-styrene copolymers (ABS resins), polyvinyl chloride resins, fluorine resins, poly(meth)acrylic resins, polycarbonate resins, polyester resins such as polyethylene terephthalate and polyethylene naphthalate, polyamide resins such as various nylons, polyimide resins, polyamideimide resins, polyarylphthalate resins, silicone resins, polysulfone resins, polyphenylene sulfide resins, polyethersulfone resins, polyurethane resins, acetal resins, cellulose resins, and polyvinyl alcohol resins can be used. In the present invention, it is preferable to use films or sheets of polypropylene resins, polyester resins, and polyamide resins among these. These may be used alone or in combination of two or more.
[0085] When forming the film or sheet, various plastic compounding agents and additives can be added to the film or sheet for the purpose of improving the processability, heat resistance, weather resistance, mechanical properties, dimensional stability, oxidation resistance, slipperiness, release properties, flame retardancy, mold resistance, electrical properties, strength, etc. of the film, and the amount of the additives added can be determined arbitrarily depending on the purpose. As the additives, lubricants, crosslinking agents, antioxidants, ultraviolet absorbers, light stabilizers, fillers, antistatic agents, lubricants, antiblocking agents, colorants such as dyes and pigments, modifying resins, and the like can be used arbitrarily.
[0086] Composition D of the present invention can be suitably used in fields such as adhesives for polypropylene substrates, heat seal adhesives for packaging materials, and coating materials, and therefore the laminate of the present invention is preferably a food packaging material containing a heat seal adhesive.
[0087] The method for forming the laminate of the present invention may be such that composition D is laminated onto at least one layer 3 selected from the group consisting of metal foil, an inorganic vapor deposition film layer, and a thermoplastic resin, and polypropylene base layer 1 is bonded to cured layer 2 of the composition by heat sealing. The temperature condition for the heat sealing is preferably 140° C. or less, more preferably 120° C. or less, from the viewpoint of the appearance of polypropylene base layer 1, and further preferably 100° C. or less. EXAMPLES
[0088] EXAMPLES The present invention will be specifically described below with reference to examples and comparative examples, but the present invention is not limited to these examples. In the examples and comparative examples, "parts" and "%" respectively mean "parts by mass" and "% by mass". Furthermore, the numerical values for each component in the tables respectively mean parts by mass.
[0089] [Physical property measurement and evaluation methods] (1) Method for measuring weight average molecular weight [Mw] and molecular weight distribution [Mw / Mn] of olefin polymer A 5 mg of a sample of olefin polymer A was collected in a 10 mL vial, and 5 g of tetrahydrofuran containing 250 ppm of dibutylhydroxytoluene as a stabilizer was added and completely dissolved at 50°C. After cooling to room temperature, the mixture was filtered through a filter with a pore size of 0.45 μm to prepare a sample solution with a polymer concentration of 0.1% by weight. Next, GPC measurement was performed using a GPC HLC-8020 manufactured by Tosoh Corporation, which was equipped with a guard column TSKguardcolumnHXL-H on a TSKgel GMHXL-L (30 cm x 2 columns) as a column. The measurement conditions were as follows: injection amount of sample solution: 50 μL, column temperature: 40°C, solvent: tetrahydrofuran, and flow rate: 1.0 mL / min. The molecular weight was determined by measuring a commercially available monodisperse polystyrene standard sample as a standard sample, and creating a calibration curve from the retention time and molecular weight of the standard sample to calculate the weight average molecular weight [Mw] and molecular weight distribution [Mw / Mn] of polymer A having a structural unit derived from an olefin monomer.
[0090] (2) Method for measuring the melting point [Tm] of polymer A having structural units derived from olefin monomers Measurement was performed using a differential scanning calorimeter DSC 220C manufactured by Seiko Instruments Inc. 5±1 mg of a sample of polymer A having a structural unit derived from an olefin monomer was placed in an aluminum pan, covered with an aluminum lid, and an empty aluminum pan was placed on the detector as a reference. The temperature was raised to 200°C at a rate of 100°C / min. After holding at the same temperature for 5 minutes, it was cooled at a rate of 10°C / min, and the amount of heat was detected at 0.5 second intervals to -10°C. After holding at the same temperature for 1 minute, it was raised to 200°C at a rate of 10°C / min, and the amount of heat was detected at 0.5 second intervals. For each sample, one exothermic peak was observed during the cooling process and one endothermic peak was observed during the final heating process. The peak top temperature during the final heating process was determined as the melting point [Tm] of polymer A having structural units derived from olefin monomers.
[0091] (3) Method for measuring average particle size of aqueous resin dispersion The average particle size of the aqueous resin dispersion was measured using a concentrated particle size analyzer FPAR-1000 (product name, manufactured by Otsuka Electronics Co., Ltd.) The results are shown in Table 1.
[0092] (4) Method for measuring elastic modulus and breaking elongation of coating film after drying of aqueous resin dispersion The aqueous resin dispersion was applied to a glass substrate whose surface had been degreased with isopropanol with an applicator to a thickness of 300 μm. The coating was then dried for 30 minutes in a safe-bend dryer set at 80°C to obtain a coating film of the aqueous resin dispersion after drying with a thickness of 100 μm. The resulting coating film after drying was sheared to 30 mm x 5 mm, and a tensile test was performed using a Shimadzu EZ small tabletop tester at a measurement temperature of 23°C, a tensile speed of 50 mm / min, and a chuck distance of 10 mm. The elastic modulus and breaking elongation of the coating film after drying of the aqueous resin dispersion were obtained from the obtained stress-strain curve. The results are shown in Table 1.
[0093] (5) Method for evaluating adhesion test of composition D to polyolefin substrate layer 1 and layer 3 To the untreated surface (surface not subjected to corona treatment) of a thermoplastic resin OPP film (PYLEN (registered trademark), Film-OT P2108 (product name), manufactured by Toyobo Co., Ltd.) to form layer 3, 100 parts of aqueous resin dispersion C and 7 parts of a siloxane-based substrate wetting agent (TEGO (registered trademark), Wet KL 245 (product name), manufactured by Evonik Co., Ltd.) were mixed to obtain composition D. The obtained composition D was applied to the untreated surface of layer 3 with a bar coater and then dried at 100°C for 3 minutes to obtain a test piece having a thickness of 10 μm (10 g / m2) of layer 3, which was an untreated OPP film made of thermoplastic resin, and layer 2 of the cured product of the composition. Furthermore, a film of the same type as the OPP film was used as the polypropylene base layer 1, and the untreated surface of the film was heat-sealed to the surface of the cured layer 2 of the composition of the obtained test piece using a heat sealer at the temperature shown in Table 2 for 10 seconds under a load of 1 kg, thereby obtaining a laminate. A test piece having a width of 15 mm was taken from the obtained laminate, and the interface between the polypropylene base layer 1 and the polypropylene base material (1) was peeled off from the end of the test piece by 90-degree peeling using a tensile tester to measure the peel strength of composition D (measurement conditions: in an atmosphere of 23°C and 65% RH, tensile speed of 50 mm / min), and the adhesion test of composition D to the polyolefin base layer 1 and layer 3 was evaluated according to the following evaluation criteria. The evaluation results are shown in Table 2. (Evaluation Criteria) A: Peel strength is 2.00N / 15mm or more and adhesion is excellent. B: The peel strength is 1.00 N / 15 mm or more and less than 2.00 N / 15 mm, and the adhesion is good. C: The peel strength is less than 1.00 N / 15 mm and the adhesion is poor.
[0094] [Production Example 1] Production of Water-Based Resin Dispersion (1) In a flask equipped with a stirrer, a reflux condenser and a temperature controller, 333.3 parts (100 parts in solids) of Aptlock (registered trademark) BW-5683 (manufactured by Mitsubishi Chemical Corporation: solids content 30.0%, weight average molecular weight 210000, molecular weight distribution 2.2, melting point 70 ° C.) as a dispersion of polymer A having a structural unit derived from an olefin monomer, and 115.4 parts of deionized water were charged and heated to 50 ° C. Next, 41.5 parts of 2-ethylhexyl acrylate (2EHA), 6 parts of styrene (ST), and 2.5 parts of glycidyl methacrylate (GMA) were charged as radical polymerizable monomers and held for 1 hour. Furthermore, 0.05 part of Perbutyl (registered trademark) H69 (trade name, manufactured by NOF Corporation, solid content 69%) as an initiator, 0.0001 part of ferrous sulfate as a reducing agent, 0.00014 parts of ethylenediaminetetraacetic acid (EDTA), 0.04 part of sodium isoascorbate monohydrate, and 0.5 parts of deionized water were added to initiate polymerization. After detecting the exothermic peak of polymerization, 0.05 parts of Perbutyl (registered trademark) H69 and 10 parts of deionized water were added dropwise over 30 minutes. After the completion of the addition, the mixture was aged at 60°C for 30 minutes to obtain an aqueous resin dispersion (1) with a 50% average particle size of 110 nm. The results are shown in Table 1.
[0095] [Production Examples 2 to 5, 8, and 9] Production of Water-Based Resin Dispersions (2) to (5), (8), and (9) Aqueous resin dispersions (2) to (5), (8), and (9) were obtained by carrying out the same operation as in Production Example 1, except that the constitutional units derived from the radical polymerizable monomer were changed as shown in Table 1. The results are shown in Table 1.
[0096] [Production Example 6] Production of Water-Based Resin Dispersion (6) 41.5 parts of 2-ethylhexyl acrylate (2EHA) as radical polymerizable monomers, 6 parts of styrene (ST), 2.5 parts of glycidyl methacrylate (GMA), 20 parts of deionized water, and 5 parts of Newcol 707SF (manufactured by Nippon Nyukazai Co., Ltd., solid content 30%, polyoxyethylene polycyclic phenyl ether sulfate) as a surfactant were emulsified in a homomixer (manufactured by Primix Corporation, homomixer MART II) to obtain a pre-emulsion. 80.4 parts of deionized water and 75 parts of the obtained pre-emulsion were placed in a flask equipped with a stirrer, a reflux condenser, and a temperature control device, and the temperature was raised to 50°C. After maintaining the mixture for 1 hour, 0.05 part of Perbutyl (registered trademark) H69 (trade name, manufactured by NOF Corporation, solid content 69%) as an initiator, 0.0001 part of ferrous sulfate as a reducing agent, 0.00014 parts of ethylenediaminetetraacetic acid (EDTA), 0.04 part of sodium isoascorbate monohydrate, and 0.5 parts of deionized water were added to initiate polymerization. After detecting the exothermic peak of the polymerization, 0.05 parts of Perbutyl (registered trademark) H69 and 10 parts of deionized water were added dropwise over 30 minutes. After the completion of the dropwise addition, the mixture was aged at 60°C for 30 minutes. After cooling, 333.3 parts of Aptlock (registered trademark) BW-5683 were added to obtain an aqueous resin dispersion (6) which is a blend of polymer A and polymer B having a 50% average particle size of 110 nm. The results are shown in Table 1.
[0097] [Production Example 7] Production of Water-Based Resin Dispersion (7) As a dispersion of polymer A having a structural unit derived from an olefin monomer, 333.3 parts (100 parts of solid content) of Aptlock (registered trademark) BW-5683 (manufactured by Mitsubishi Chemical Corporation: solid content 30.0%, weight average molecular weight 210,000, molecular weight distribution 2.2, melting point 70°C) was used as an aqueous resin dispersion (7). The results are shown in Table 1.
[0098] [Examples 1 to 6, Comparative Examples 1 to 3] A laminate was prepared as shown in Table 2, and an adhesion test was carried out on the polyolefin substrate layer 1 and layer 3. The evaluation results are shown in Table 2. The abbreviations in Table 1 are as follows: Aptlock BW-5683: Olefin emulsion, manufactured by Mitsubishi Chemical Corporation EHA: Ethylhexyl acrylate, manufactured by Mitsubishi Chemical Corporation iBMA: isobutyl methacrylate, manufactured by Mitsubishi Chemical Corporation tBMA: t-butyl methacrylate, manufactured by Mitsubishi Chemical Corporation ST: Styrene, manufactured by NS Styrene Monomer Co., Ltd. GMA: glycidyl methacrylate, manufactured by Mitsubishi Chemical Corporation
[0099] [Table 1]
[0100] [Table 2]
[0101] In Table 2, OPP means oriented polypropylene film.
[0102] In Examples 1 to 6, an aqueous resin dispersion was used in which polymer A and polymer B were contained in the same particle, and the elastic modulus of the coating film obtained by drying the aqueous resin dispersion C at 80°C was within the range specified in the present application, and therefore the adhesion to the polyolefin substrate layer 1 and layer 3 was good. In Comparative Example 1, an aqueous resin dispersion was used in which the elastic modulus of the coating film obtained by drying the aqueous resin dispersion at 80°C was outside the range specified in the present application, and therefore the adhesion to the polyolefin substrate layer 1 and layer 3 was poor. In Comparative Example 2, an aqueous resin dispersion was used which was a blend not containing polymer A and polymer B in the same particle, and therefore the adhesion to the polyolefin substrate layer 1 and layer 3 was poor. In Comparative Example 3, an aqueous resin dispersion was used which did not contain polymer B in the same particle, and therefore the adhesion to the polyolefin substrate layer 1 and layer 3 at 100°C was poor. [Industrial Applicability]
[0103] According to the present invention, it is possible to provide an adhesive using an aqueous resin dispersion that has excellent low-temperature heat sealability to polyolefin substrates and that easily has excellent adhesion to polyolefin substrates by heating at low temperature for a short time, and a laminate containing a dried product of the adhesive. Therefore, the adhesive of the present invention can be suitably used in fields such as adhesives for polypropylene substrates, heat seal adhesives for packaging materials, and paints, and is extremely important industrially. [Explanation of symbols]
[0104] 10...laminate, 11...food packaging material, 1...layer 3, 2...layer 2, 3...layer 1
Claims
1. An aqueous resin dispersion C comprising a polymer A having a structural unit derived from an olefin-based monomer and a polymer B having a structural unit derived from a radical polymerizable monomer within the same particle, the aqueous resin dispersion C being dried at 80° C. for 30 minutes to give a coating film having an elastic modulus of more than 0 MPa and not more than 35 MPa.
2. 2. The aqueous resin dispersion C according to claim 1, wherein the coating film obtained by drying the aqueous resin dispersion C at 80° C. for 30 minutes has a breaking elongation of 100% or more and 3000% or less.
3. 3. The aqueous resin dispersion C according to claim 1, wherein the coating film obtained by drying the aqueous resin dispersion C at 80° C. for 30 minutes has a breaking elongation of 800% or more and 3000% or less.
4. The aqueous resin dispersion C according to any one of claims 1 to 3, wherein the mass ratio of the structural units derived from aromatic monomers to the total structural units of the polymer B is 1.0 mass% or more and 30.0 mass% or less.
5. A composition D comprising the aqueous resin dispersion C according to any one of claims 1 to 4.
6. 6. Composition D according to claim 5, wherein said composition D is a heat seal adhesive for polyolefin substrates.
7. The composition D according to claim 5 or claim 6, wherein a mass ratio of the polymer A to a total mass of the polymer A and the polymer B is 30 mass% or more.
8. Composition D according to any one of claims 5 to 7, wherein the olefinic monomer comprises propylene.
9. The composition D according to any one of claims 5 to 8, wherein the glass transition temperature of the polymer B is -80°C or higher and 20°C or lower.
10. The composition D according to any one of claims 5 to 9, wherein the glass transition temperature of the polymer B is -80°C or higher and lower than -3°C.
11. A laminate comprising a dried product of composition D according to any one of claims 5 to 10.
12. The laminate according to claim 11, comprising a polypropylene base layer 1, a layer 2 made of the dried product of said composition D, and at least one layer 3 selected from the group consisting of a metal foil, an inorganic vapor deposition film layer, and a thermoplastic resin layer, laminated in this order.
13. A food packaging material comprising composition D of claim 6.
Citation Information
Patent Citations
Aqueous dispersion
CN108299658A
Adhesive composition and heat seal adhesion material using this
JP2002105418A
Aqueous dispersion
JP2009108128A
Aqueous resin dispersion, method for producing aqueous resin dispersion, aqueous coating material, and adhesive
WO2019112039A1
Heat-sealing adhesive composition
JP2001179909A
